AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN LEARNING SPEAKING IN WATNAMOM SCHOOL, THAILAND - Walisma, Maghfiratul; Syahputra, Andi; Husna, Faizatul; Al Ubaids, Azrial Rizky (Journal of English Educational Study (JEES), 2025)
This study aims to examine the factors that lead to students' difficulties in learning to speak English at Watnamom School and to identify the types of challenges they face in improving their speaking skills. A mixed-method approach was used, combining quantitative surveys and qualitative interviews with students and teachers. The findings reveal that students struggle with confidence issues, fear of making mistakes, and a lack of exposure to English-speaking environments. Additionally, linguistic barriers, such as vocabulary limitations and pronunciation difficulties, further hinder their progress. Instructional challenges, including teacher-centered methods and limited speaking practice, also contribute to their struggles. Environmental factors, such as minimal opportunities to practice English outside the classroom, further exacerbate the issue. These results suggest that a more interactive and supportive learning environment, incorporating group discussions, role-plays, and real-world speaking opportunities, is essential to help students develop their English-speaking skills. Addressing these challenges can enhance students' confidence and fluency, preparing them for both academic and professional success.